A Catalytic Diastereoselective Formal [5+2] Cycloaddition Approach to Azepino[1, 2‐a]indoles: Putative Donor–Acceptor Cyclobutanes as Reactive Intermediates1. Issue 50 (22nd October 2014) - Shenje, Raynold; Martin, M. Cynthia; France, Stefan
Abstract A catalytic formal [5+2] cycloaddition approach to the diastereoselective synthesis of azepino[1, 2‐a]indoles is reported. The reaction presumably proceeds through a Lewis acid catalyzed formal [2+2] cycloaddition of an alkene with an N‐indolyl alkylidene β‐amide ester to form a donor–acceptor cyclobutane intermediate, which subsequently undergoes an intramolecular ring‐opening cyclization. Azepine products are formed in up to 92 % yield with high degrees of diastereoselectivity (up to 34:1 d.r.).